2020
DOI: 10.3390/cryst11010016
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Bis(nickelation) of 1,1′-Bis(o-carborane)

Abstract: The metalation of [Tl]2[1-(1′-3′,1′,2′-closo-TlC2B9H10)-3,1,2-closo-TlC2B9H10], with the smaller {Ni(dmpe)} fragment sourced from [Ni(dmpe)Cl2], is explored. The bis(metalated) products are obtained as a diastereoisomeric mixture. These isomers were separated, fully characterised spectroscopically and crystallographically and identified as rac-[1-(1′-3′-(dmpe)-3′,1′,2′-closo-NiC2B9H10)-3-(dmpe)-3,1,2-closo-NiC2B9H10] (1) and meso-[1-(1′-3′-(dmpe)-3′,1′,2′-closo-NiC2B9H10)-3-(dmpe)-3,1,2-closo-NiC2B9H10] (2). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In contrast to other MOCHA materials with an extended metal chalcogenide core, MicroED has revealed that the synthesized carborane-structured MOCHAs consist of an unprecedented zero-dimensional Cu 4 Se 4 cluster that is representative of the smallest building block of bulk CuSe materials. This work therefore further establishes the utility of MicroED for hybrid material structure elucidation when reaching the limitations of more traditional structural determination methods. This study furthermore highlights how the use of bulky, organomimetic, boron cluster ligands can lead to the formation of hybrid materials with unique structures and properties. , , …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast to other MOCHA materials with an extended metal chalcogenide core, MicroED has revealed that the synthesized carborane-structured MOCHAs consist of an unprecedented zero-dimensional Cu 4 Se 4 cluster that is representative of the smallest building block of bulk CuSe materials. This work therefore further establishes the utility of MicroED for hybrid material structure elucidation when reaching the limitations of more traditional structural determination methods. This study furthermore highlights how the use of bulky, organomimetic, boron cluster ligands can lead to the formation of hybrid materials with unique structures and properties. , , …”
Section: Discussionmentioning
confidence: 64%
“…Carboranes, with the molecular formula of C 2 B 10 H 12 , exist as three distinct isomers ( ortho -, meta -, para -) distinguished by the relative orientation of the two carbon vertices. Importantly, the electronic nonuniformity of ortho - and meta -carboranes, resulting from the asymmetry introduced by the carbon vertices, has allowed for the precise modulation of metal surface and metal center properties, as determined by the relative positioning of ligating substituents on the sterically invariant boron clusters (Figure b). This electronic nonuniformity is further exemplified by the regioselective chemistry of carboranes that has permitted selective introduction of functional groups to the carbon-based vertices and various boron-based vertices of carboranes. …”
Section: Introductionmentioning
confidence: 99%
“…In this case, the barrier to rotation of the dicarbollide ligand around the M–B(1) axis is sufficiently high, which leads to the appearance of two signals in the 31 P NMR spectra even in the presence of two identical phosphine ligands or a symmetrical bidentate phosphine ligand. In addition, the 1 H NMR spectrum shows splitting of the signal of the CH group of the dicarbollide ligand due to its interaction with the phosphorus atom of one of the phosphine ligands Strong interactions of a repulsive nature are present, leading to a skeletal rearrangement with the migration of a substituted carbon atom to the lower belt of the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the presence of two phenyl substituents at the carbon atoms of the dicarbollide ligand leads to skeletal rearrangement in the course of the formation of nickelacarboranes, regardless of the size of the phosphine ligands used . On the other hand, even with bulky substituents such as carboranyl or metallacarboranyl groups, the rearrangement can be avoided by using phosphine ligands with a low Tolman angle or bite angle for bidentate phosphines . At the same time, the above examples concern limiting cases (the presence of two rather large or one very large substituent), while there are no data on the effect of smaller simple substituents in dicarbollide ligands on the nature of the resulting nickelacarboranes.…”
Section: Introductionmentioning
confidence: 99%
“…Mandal was one of Alan Welch's PhD students, and his work is on bis(nickelation) of bis(o-carborane), which forms diastereoisomeric mixtures on metalation of the second carborane cage and additionally undergoes isomerisation. It was found that stereospecificity was influenced by intramolecular dihydrogen bonding, whereas a specific isomerisation outcome was related to the stereo-electronic nature of bis(phosphine) ligands [3].…”
mentioning
confidence: 99%